Neurotrophic Factors NGF, GDNF and NTN Selectively Modulate HSV1 and HSV2 Lytic Infection and Reactivation in Primary Adult Sensory and Autonomic Neurons - Andy A. Yanez; Telvin Harrell; Heather J. Sriranganathan; Angela M. Ives; Andrea S. Bertke (Pathogens, 2017)
Herpes simplex viruses (HSV1 and HSV2) establish latency in peripheral ganglia after ocular or genital infection, and can reactivate to produce different patterns and frequencies of recurrent disease. Previous studies showed that nerve growth factor (NGF) maintains HSV1 latency in embryonic sympathetic and sensory neurons. However, adult sensory neurons are no longer dependent on NGF for survival, some populations cease expression of NGF receptors postnatally, and the viruses preferentially establish latency in different populations of sensory neurons responsive to other neurotrophic factors (NTFs). Thus, NGF may not maintain latency in adult sensory neurons. To identify NTFs important for maintaining HSV1 and HSV2 latency in adult neurons, we investigated acute and latently-infected primary adult sensory trigeminal (TG) and sympathetic superior cervical ganglia (SCG) after NTF removal. NGF and glial cell line-derived neurotrophic factor (GDNF) deprivation induced HSV1 reactivation in adult sympathetic neurons. In adult sensory neurons, however, neurturin (NTN) and GDNF deprivation induced HSV1 and HSV2 reactivation, respectively, while NGF deprivation had no effects. Furthermore, HSV1 and HSV2 preferentially reactivated from neurons expressing GFRα2 and GFRα1, the high affinity receptors for NTN and GDNF, respectively. Thus, NTN and GDNF play a critical role in selective maintenance of HSV1 and HSV2 latency in primary adult sensory neurons.